Association between diabetes mellitus and the risk for major cardiovascular outcomes and all-cause mortality in women compared with men: a meta-analysis of prospective cohort studies. Issue 7 (17th July 2019) - Wang, Hao; Ba, Ying; Cai, Run-Ce; Xing, Qian
Abstract : Objective: Previous studies have reported sex differences in associations between diabetes mellitus (DM) and the risk of developing coronary heart disease (CHD) and stroke; however, the risk for cardiac death and all-cause mortality in women compared with men has not been reported. Therefore, this quantitative meta-analysis was performed to provide reliable estimates of sex differences in the effect of DM on major cardiovascular outcomes and all-cause mortality, irrespective of DM type. Design: Meta-analysis. Data sources: The PubMed, Embase and the Cochrane Library databases were systematically searched in April 2018. Eligibility criteria: Investigations designed as prospective cohort studies that examined the association between DM and major cardiovascular outcomes and all-cause mortality stratified according to sex were included. Data extraction and synthesis: Data extraction and quality assessment were independently performed by 2 of the authors, and the relative risk ratio (RRR) obtained using a random effects model was used to measure sex differences in the associations of DM with major cardiovascular outcomes and all-cause mortality. Results: Thirty prospective cohort studies that reported data from 1 148 188 individuals were included. The pooled women-to-men RRR suggested that female sex was associated with an increased risk for CHD (RRR 1.52(95% CI 1.32 to 1.76); p<0.001), stroke (RRR 1.23(95% CI 1.09 to 1.39); p=0.001), cardiac death (RRR 1.49(95% CI 1.11 to 2.00); p=0.009) and all-cause mortality (RRR 1.51(95% CI 1.23 to 1.85); p<0.001). In addition, sex differences for the investigated outcomes in the comparison between DM and non-DM patients were variable after stratification of studies according to publication year, country, sample size, assessment of DM, follow-up duration, adjustment for important cardiovascular risk factors and study quality. Conclusions: Findings of the present study suggested that women with DM had an extremely high risk for CHD, stroke, cardiac death and all-cause mortality compared with men with DM.